Assessing post-competition recovery in judo: insights into muscle damage and performance - Campos, B. T.; Penna, E. M.; Ogando, P. H. M.; Rodrigues, J. G. S.; Albuquerque, M. R.; Nakamura, F. Y.; Prado, L. S. (Research in Sports Medicine, 2025)
Recovery dynamics in combat sports like judo are critical for optimizing performance and reducing injury risk. This study aimed to evaluate the time-course of physiological (creatine kinase, CK) and neuromuscular (countermovement jump, CMJ) recovery in junior judo athletes following competition. Thirteen junior-level judo athletes participated in this study. Assessments of CK and CMJ were conducted at three points: 24 hours before, 24 hours after, and 48 hours after competition. A repeated-measures ANOVA was used to analyse differences across time points, and Pearson`s correlation measured associations between match duration and recovery markers. CK levels showed a significant increase 24 hours post-competition, returning to baseline by 48 hours, indicating muscle damage peaks shortly after matches. CMJ performance remained stable across all time points, suggesting a different recovery pathway for neuromuscular function. Additionally, match duration correlated with CK increase, reflecting higher physical stress. This study highlights a distinct recovery pattern for CK and CMJ, with CK peaking 24 hours post-match and CMJ showing resilience to acute competition stress. Coaches and athletes can use these findings to tailor recovery interventions, focusing on muscle recovery within the first 24 hours to optimize performance and reduce injury risk in subsequent events.